2015
DOI: 10.1016/j.nbd.2014.09.020
|View full text |Cite
|
Sign up to set email alerts
|

A new humanized ataxin-3 knock-in mouse model combines the genetic features, pathogenesis of neurons and glia and late disease onset of SCA3/MJD

Abstract: Spinocerebellar ataxia type 3 (SCA3/MJD) is a neurodegenerative disease triggered by the expansion of CAG repeats in the ATXN3 gene. Here, we report the generation of the first humanized ataxin-3 knock-in mouse model (Ki91), which provides insights into the neuronal and glial pathology of SCA3/MJD. First, mutant ataxin-3 accumulated in cell nuclei across the Ki91 brain, showing diffused immunostaining and forming intranuclear inclusions. The humanized allele revealed expansion and contraction of CAG repeats in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 49 publications
7
66
0
Order By: Relevance
“…Among them, Serpina3n and Lcn2 were further validated as strongly, but transiently induced following LPS injection or MCAO (Zamanian et al, ). They are also induced in other disease models (Itoh et al, ; Suk, ; Switonski, Szlachcic, Krzyzosiak, & Figiel, ). Change in transcriptome is a conserved feature of astrocyte reaction, similarly observed in Drosophila glia (Lu et al, ).…”
Section: What Are the Defining Features Of Reactive Astrocytes?mentioning
confidence: 88%
“…Among them, Serpina3n and Lcn2 were further validated as strongly, but transiently induced following LPS injection or MCAO (Zamanian et al, ). They are also induced in other disease models (Itoh et al, ; Suk, ; Switonski, Szlachcic, Krzyzosiak, & Figiel, ). Change in transcriptome is a conserved feature of astrocyte reaction, similarly observed in Drosophila glia (Lu et al, ).…”
Section: What Are the Defining Features Of Reactive Astrocytes?mentioning
confidence: 88%
“…Despite evidence of variable Purkinje cell degeneration in MJD patients and models, 47,48 this could lead to exacerbation of the disease in these cells compared with what is observed in human neuropathology, and therefore the observations may actually be even more relevant in the context of pure SCAs, in which the neurodegeneration occurs primarily in Purkinje cells. However, this conclusion was based on the exploration of a particular MJD mouse model with selective overexpression of mutant ataxin-3 in the cerebellum, in contrast to the more widespread expression in MJD patients.…”
Section: Discussionmentioning
confidence: 98%
“…Subsequently, Padmanabhan et al reported that anti‐chymotrypsin induces tau phosphorylation in neurons. In various neurological diseases, the expression of SERPINA3N in the brain has been found to be significantly upregulated . Recent studies have also shown that SERPINA3N is clearly related to many inflammation‐related diseases, such as hypothalamic inflammation, retinal neuroinflammation, allergic airway inflammation, myocarditis, and atherosclerosis .…”
Section: Discussionmentioning
confidence: 99%
“…Serpina3n encodes anti‐chymotrypsin, which is a widely expressed member of the serpin superfamily and has recently been recognized as a key component of the inflammatory response in the brain . In many neurological diseases, anti‐chymotrypsin in the brain has been found to be markedly upregulated . Serpina3n was also reported as a highly expressed gene in persistently active astrocytes .…”
Section: Introductionmentioning
confidence: 99%